2014
DOI: 10.1038/nature13683
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory caspases are innate immune receptors for intracellular LPS

Abstract: The murine caspase-11 non-canonical inflammasome responds to various bacterial infections. Caspase-11 activation-induced pyroptosis, in response to cytoplasmic lipopolysaccharide (LPS), is critical for endotoxic shock in mice. The mechanism underlying cytosolic LPS sensing and the responsible pattern recognition receptor are unknown. Here we show that human monocytes, epithelial cells and keratinocytes undergo necrosis upon cytoplasmic delivery of LPS. LPS-induced cytotoxicity was mediated by human caspase-4 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

46
1,904
5
12

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,841 publications
(1,967 citation statements)
references
References 38 publications
46
1,904
5
12
Order By: Relevance
“…Basal expression of CASP4 is low in resting cells and its expression and activity are triggered by bacterial factors such as intracellular lipopolysaccharide [27,28]. To determine if B. cenocepacia infection of WT macrophages induces CASP4 protein expression, macrophages were infected with bacteria for 2 h or 6 h and the expression of CASP4 was evaluated by immunoblot.…”
Section: Resultsmentioning
confidence: 99%
“…Basal expression of CASP4 is low in resting cells and its expression and activity are triggered by bacterial factors such as intracellular lipopolysaccharide [27,28]. To determine if B. cenocepacia infection of WT macrophages induces CASP4 protein expression, macrophages were infected with bacteria for 2 h or 6 h and the expression of CASP4 was evaluated by immunoblot.…”
Section: Resultsmentioning
confidence: 99%
“…This represents a novel mechanism for inflammasome activation that is distinct from LPS sensing and activation of caspase-1. 58 In contrast to the roles of other inflammatory cytokines, caspase-12 can abrogate the inflammatory response in mice by inhibiting caspase-1, in a protease-independent function. 59 As a result, mice deficient for caspase-12 show increased bacterial clearance and resistance to sepsis.…”
Section: Caspases In Inflammation and Immunitymentioning
confidence: 99%
“…Initial work has identified the pro‐inflammatory cytokine interleukin (IL)‐1β as a key substrate of caspase‐1 (Thornberry et al , 1992). Subsequently, it was found that caspase‐1, as well as caspase‐11 and its human orthologs caspase‐4 and caspase‐5, induces a novel programmed cell death pathway that is characterized by cell swelling, lysis, and the release of cytoplasmic content (Fink & Cookson, 2007; Kayagaki et al , 2011; Shi et al , 2014), presumably as a result of the formation of membrane pores (Fink et al , 2008). Since this type of cell death is morphologically distinct from apoptosis and intrinsically pro‐inflammatory, it was named pyroptosis, from the Greek pyro (fire or fever) and ptosis (to fall) (Bergsbaken et al , 2009).…”
Section: Introductionmentioning
confidence: 99%